Practical Experience Utilizing a Rapid Review Process for Nursing Practice Decision-Making on Pressure Injury Outcome Indicators - Kong Yuke Lin; Nur Azmiah Zainuddin; Salbiah Sindot; Zahidah Idris; Gowry Narayanan; Anny Mary S Joseph @Soosai; Devi K Saravana Muthu (Asian Journal of Medicine & Health Sciences, 2023)
Rapid review is a method to yield evidence in a timely and systematic manner. We used this method to identify internationally comparable outcome indicators for monitoring pressure injury. This paper aims to illustrate our experience with the rapid review methodology for decisionmaking in nursing practice. A rapid review (Review 1) on pressure injury outcome indicators was performed using four databases (PUBMED, CINAHLPlus, EMBASE, and MEDLINE) for publications from 2010 to 2019. Article screening was conducted independently by two reviewers using the PRISMA guideline. The views of the collaborative review team, local experts, and knowledge users were taken into account throughout the study. The evidence obtained from the rapid review was found to be insufficient, therefore, additional searches using reference lists (Review 2) and grey literature (Review 3) were required. Screening, data extraction, were conducted independently and verified. A narrative synthesis was performed based on the data extracted. This research investigates how to obtain nursing evidence efficiently using the rapid review method while adapting it to a specific context through supplementary searches. Although the rapid review is a cost-effective way to synthesize nursing evidence, it is crucial to collaborate closely with local experts and knowledge users to ensure its relevance. Effective decision-making relies on collaboration between the review team, stakeholders, and reviewers' ability to assimilate the rapid review process and adapt it appropriately to the local context, in order to obtain relevant evidence. This process highlighted the importance of a dynamic, contextualized, and collaborative approach in using research to inform decision-making.